PENGARUH PENGETAHUAN PRODUK TABUNGAN, CITRA PERBANKAN DAN PERSEPSI MENGENAI SUKU BUNGA SIMPANAN TERHADAP KEPUTUSAN MENABUNG (Studi Kasus pada Bank BRI Unit Selayo) - Nia Yolanda; Rita Dwi Putri; Nidia Anggreni (Journal of Innovation Research and Knowledge, 2022)
Bank BRI Selayo Unit is one of BRI's work units. Bank BRI Unit Selayo always strives to improve the quality of service to its customers so that they are satisfied with the services provided. From interviews conducted by researchers with several customers at Bank BRI Unit Selayo, the reason for saving at Bank BRI Unit Selayo is because Bank BRI is a government-owned bank so that customers feel safe, there is a sense of customer trust in the bank, opening an account is easy and practical, many do a lottery so that you have a chance of a prize, have offices spread throughout Indonesia to remote areas, many products offered, interest benefits if you have savings. This type of research is a causative research with the data sources used in this study in the form of a questionnaire distributed and filled out by the customers of BRI Selayo Unit. The population of this research is customers who have savings in Bank BRI Unit Salayo with a total sample of 100 people. The test results show that knowledge of savings products has no effect on saving decisions as evidenced by using t count 0.571 < t table value 1.98638 and significant 0.570 > 0.05. Banking image has an effect on saving decisions with t count 3.618 > t table value 1.98638 and significant 0.0000 <0.05. Perceptions of deposit interest rates affect the decision to save with t count 4.508 > t table value 1.98638 and significant 0.000 <0.05. The results show that knowledge of savings products, banking image and perception of deposit interest rates simultaneously have an influence on saving decisions as evidenced by using F arithmetic of 15.100 > F table 2.70 with a significance level of 0.000 because the probability is much smaller than 0.05